Enhancing Marriage Age Awareness through Comprehensive Sexuality Education: A Multicultural Approach in Rural Aluh-Aluh Besar, Kabupaten Banjar, Indonesia - Sa'adah, Sa'adah; Sairazi, Abdul Hafiz (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This research examines the attitudes and perceptions of early marriage within Aluh-aluh Besar Village, South Kalimantan, and evaluates the potential of a multicultural approach in comprehensive sexuality education. The study aims to understand the cultural, emotional, and socio-economic factors that influence early marriage decisions and explore how integrating diverse cultural perspectives can enhance sexual education programs. Using a mixed-methods approach, including surveys and interviews with community members and educators, the research gathers insights into local traditions, the emotional benefits perceived from early marriage, and the role of employment and multiculturalism in shaping these views. Findings indicate that early marriage is deeply rooted in cultural traditions and is often seen as providing emotional stability and protection from perceived risks. Economic stability and multicultural factors also play significant roles in its acceptance. The study highlights the need for culturally sensitive educational programs that address these factors and promote informed decision-making about the appropriate age for marriage. The evaluation underscores the importance of incorporating diverse cultural perspectives to effectively implement comprehensive sexuality education. The findings suggest that socioeconomic, biological, and cultural factors influence the awareness of the appropriate age for marriage, and the lack of such awareness can lead to adverse outcomes. The study concludes that addressing these issues requires a comprehensive approach, including education, legal reforms, and cultural shifts, while also considering the role of personal responsibility in decision-making.